Managerial Judgement Versus Financial Techniques in Strategic Investment Decisions: An Empirical Study on the Syrian Coastal Region Firms - Mahmoud, Oubay (International Journal of Business, Economics and Management, 2016)
While there has been extensive research on the use of financial appraisal techniques [Pay Back (PB), Return on Capital Employed (ROCE), Internal Rate of Return (IRR) and Net Present Value (NPV)] in Strategic Investment Decisions (SIDs), little research has been conducted on the role of the Managerial Judgement factors (MJ factors) – past experience, intuition and own judgement - in the SIDs. In practice, many investments are undertaken on the basis of financial returns with little or no analysis of the growth options embedded in the proposed investments. Essential to considering these options in the SIDs is the deployment of MJ factors in the SIDs. This research draws on a 36-firm survey of finance directors in Syrian coastal region firms to set out the relative importance of the MJ factors and financial techniques in the SIDs. The findings from the survey show high usage of the MJ factors in the SIDs but not at the expense of the financial techniques usage which are used regardless of the MJ adoption in the SIDs. However, There is a tendency towards using MJ factors more than financial techniques for investments with growth options. There is no relationship between neither the ownership nor the sector with the MJ adoption. ROCE and PB are the most frequently used financial techniques.